Chemical and biological control of Sclerotinia stem rot in the soybean crop - Sumida,Ciro Hideki (2015)
It was evaluated the effect of fungicides and the microbial control agent Trichoderma harzianum on the inhibition of the carpogenic and ascospore germination of Sclerotinia sclerotiorum. This study also evaluated the chemical, fungicidal and microbial control of white mold or Sclerotinia stem rot of soybean in the field. Three experiments were conducted, as follows: 1) inhibition of carpogenic germination of sclerotia, 2) inhibition of ascospore germination, and 3) control of Sclerotinia stem rot in a soybean crop under field conditions. The treatments evaluated were fluazinam, procymidone, iprodione, thiophanate-methyl, carbendazim, benzalkonium chloride + fluazinam, and T. harzianum. Procymidone resulted in an inhibition of 13.5% and benzalkonium chloride in an inhibition of 13.9% in an ascospore germination test. Fluazinam and procymidone were the most effective in reducing the production of ascospores/apothecium, representing 65.6% and 82.4% of inhibition. Procymidone and fluazinam if combined or not with benzalkonium chloride were the most effective in controlling sclerotinia stem rot under field conditions when applied at the onset of flowering and 15 days later. In the 2009-10 harvest, these two fungicides reduced the incidence of Sclerotinia stem rot by 73.1 and 71.6% and in the 2010-11 harvest by 75.7 and 77.6%, respectively.